Dynamic properties of fast and slow skeletal muscles in the cat and rat following cross-reinnervation. - Luff, A R (1975)
1. Cross-reinnervation was performed between the slow-twitch soleus (SOL) and fast-twitch extensor digitorum longus (EDL) muscles in the cat and the SOL and fast-twitch flexor hallucis longus (FHL) muscles in the rat. The isometric and force-velocity properties of the muscles were subsequently determined. 2. As a result of cross-reinnervation the dynamic properties of both slow- and fast-twitch muscles in the cat were considerably altered. The isometric twitch time to peak was 33-9 msec in the X-SOL compared with 84-7 msec in the N-SOL. The intrinsic speed of shortening and a/P0 values were 25-4 mum. sec-1 and 0-34 respectively in the X-SOL and 14-4 mum. sec-1 and 0-20 in the N-SOL. In the X-EDL the twitch time to peak was 52-6 msec compared with 23-4 msec in the N-EDL; the intrinsic speed of shortening and a/P0 values were 14-1 mum. sec-1 and 0-29 respectively, whereas they were 31-9 mum. sec-1 and 0-44 in the N-EDL. 3. In the rat X-SOL there was shortening of the isometric twitch time to peak from 39-5 msec in the N-SOL to 19-7 msec and an increase in the intrinsic speed of shortening from 17-7 mum. sec-1 to 32-3 mum. sec-1, although over most of the force-velocity curve the X-SOL values were only slightly greater than those for N-SOL. The force-velocity data for the X-SOL muscles could not be fitted by Hill's equation. 4. The isometric and force-velocity results of the X-SOL of the rat suggested that the muscle contained a significant proportion of slow fibres. An examination of the motor unit characteristics of the N-FHL showed the presence of approximately 14% small, slow units. 5. It is concluded that there are no fundamental differences between the rat and the cat with regard to the effect of cross-reinnervation on hind-limb muscles. However, these, and previously published results, suggest that there may be important differences between heterologous muscles in the degree of influence that their respective motor nerves can exert on an alien muscle.